A wardrobe suitable for a virtuous pauper - Marinčič, Katarina (Vestnik za tuje jezike, 2019)
The subject of this paper is not the influence of Pierre de Marivaux's La Vie de Marianne upon Samuel Richardson's Pamela (a question that has been widely discussed since the 18th century). In spite of some obvious similarities, La Vie de Marianne and Pamela are two profoundly dissimilar novels. Pamela is a tale with a happy ending and a clear moral message. La vie de Marianne is an unfinished tale and, as such, morally ambiguous by its very nature. However, at crucial moments of their stories, confronted with the first attempts upon their virtue, both heroines react in accordance with their sense of propriety in clothing as well as with an acute fashion sense. In both novels, the seducer tries to lure his victim with clothes. Upon receiving the gift, both girls display a naive and joyful gratitude. Their dilemma begins when the gift of clothing turns out to be a gift of lingerie. The self-indulgent French heroine, after a short reflection, decides to keep the clothes. Pamela turns out to be a much more modern young woman. She returns the gift and - in a seemingly paradoxical way - puts herself in need of a new set of clothes.
Keywords: angleška književnost; angleški romani; francoska književnost; francoski romani; Marivaux, Pierre de; moda; oblačenje; primerjalna književnost; Richardson, Samuel; spodobnost